Karakteristik Sentigi (Pemphis acidula) Sebagai Bioindikator Lingkungan Konservasi Mangrove di Kawasan Konservasi Laut Daerah Gili Sulat Lombok Timur Indonesia - Agil Al Idrus; I Gde Mertha; Marhus Marhus; Pahmi Husain (Jurnal Penelitian Pendidikan IPA, 2023)
Sentigi (Pemphis acidula) is one of the mangrove species that is classified as pure stand so it has the potential to be used as an indicator species in the mangrove area in Gili Sulat. The research location ganti dengan Kawasan Konservasi Laut Daerah (KKLD) Gili Sulat Lombok Timur. The purpose of this study was to determine the characteristics of sentigi as environmental bioindicators in mangrove forests in Gili Sulat, East Lombok. The research method is done by delineation method using high resolution satellite imagery and ground check. Determination of the sampling point at the research location was determined using satellite imagery. The data analysis technique uses visualization analysis of satellite imagery catches and analysis of mangrove vegetation which is described descriptively. The results of this study indicate that a) species Sentigi can be identified using high resolution satellite imagery based on the color resolution quality of satellite imagery, namely high, medium and low cover. (b) Sentigi species can be used as indicator plants in the Gili Sulat mangrove community based on the characteristics of environmental factors such as habitat type, habitat altitude, pH and salinity. Conclusions from this study include: a. The distribution of the population of stands sentigi (Pemphis acidula) on Gili Sulat is unique, namely in the middle of a mangrove forest. b.population Sentigistands on Gili Sulat are grouped separately as pure stands. c. Satellite imagery can be used to identify the presence of populations sentigi on Gili Sulat. (d) The presence of sentigi can be a bioindicator of sandy environments, ecoton areas, and climax succession in Gili Sulat.